Mix Energy Source Unified Loop based Dual Active Bridge for Electric Vehicle - Jena P.; Singh R.K. (My University, 2025)
This paper presents a unified loop based dual active bridge (DAB) with front end rectifier, a boost converter forming AC to DC power stage, and a DAB forming an isolated second DC-DC stage for electric vehicle battery charging application. In unified loop controller, controller capable of power factor correction (PFC) and battery charging control without sensing the DC link voltage in the topology is proposed. In this control strategy, irrespective of the nature of input supply (AC or DC) the output voltage/current maintained constant to the desired value as per battery constant current and constant voltage (CC-CV) characteristics thus the title referred mixed energy source. This type of power stage topology is used due to the inherent nature of the rectifier to provide DC output (constant or pulsating) irrespective of input supply nature. Therefore, a combination of unified loop and mentioned topology allows constant battery voltage/current irrespective of the nature of the input. A Boost converter is used to regulate DC link voltage depending upon load requirement thus varying DC link will allow to regulate the output supply of the DAB. As per the IEC 61000-3-2 standard, the total harmonic distortion in the current drawn from the AC main is restricted to prescribed limits. In this paper mathematical modeling of the topology has been carried along with a detailed study of working of the unified loop. MATLAB/Simulink based model along with the experimental results is discussed to support the idea with both AC and DC supply. © 2020 IEEE.